2018
DOI: 10.1016/j.jhazmat.2017.08.066
|View full text |Cite
|
Sign up to set email alerts
|

In situ arsenic oxidation and sorption by a Fe-Mn binary oxide waste in soil

Abstract: In situ arsenic oxidation and sorption by a Fe-Mn binary oxide waste in soil., Journal of Hazardous Materialshttp://dx.doi.org/10. 1016/j.jhazmat.2017.08.066 This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting proof before it is published in its final form. Please note that during the production process errors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 74 publications
(22 citation statements)
references
References 53 publications
0
22
0
Order By: Relevance
“…Pre‐trial As concentrations (11.7 μg kg −1 ) in the 25% WTR–compost were significantly lower ( p < 0.05) than in the pre‐trial 12.5% compost treatment (29.3 μg kg −1 ). This is attributed to the capacity of WTR to strongly chemisorb As (Sarkar et al, 2007; McCann et al, 2018) and suggests WTR addition to an As‐rich compost could reduce bioavailable As content.…”
Section: Resultsmentioning
confidence: 99%
“…Pre‐trial As concentrations (11.7 μg kg −1 ) in the 25% WTR–compost were significantly lower ( p < 0.05) than in the pre‐trial 12.5% compost treatment (29.3 μg kg −1 ). This is attributed to the capacity of WTR to strongly chemisorb As (Sarkar et al, 2007; McCann et al, 2018) and suggests WTR addition to an As‐rich compost could reduce bioavailable As content.…”
Section: Resultsmentioning
confidence: 99%
“…As a consequence, As concentration in natural aqueous environments is essentially controlled by interactions with mineral surfaces. Composite oxides have also been developed to enhance their efficiency as oxidants and adsorbents for both As(III) and As(V) (Chakravarty et al, 2002;Feng et al, 2006a;Ma et al, 2020;McCann et al, 2018;Wu et al, 2018;Ying et al, 2012;Zhang et al, 2007;Zhang et al, 2018;Zheng et al, 2020). Manganese (Mn) oxides can also oxidize As(III) (Manning et al, 2002;Scott and Morgan, 1995), as reported in natural lacustrine environments (Oscarson et al, 1980(Oscarson et al, , 1981a(Oscarson et al, , 1981b, and Mn oxides have a key role in As geochemical cycling (Driehaus et al, 1995;Nesbitt et al, 1998;Scott and Morgan, 1995;Tournassat et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…So far, several techniques including oxidation (McCann et al., 2018), coagulation and precipitation (Cui et al., 2015), adsorption (Ren et al., 2014), ion exchange (Pakzadeh and Batista, 2011) and membrane techniques (Kang et al., 2000) have been developed and tested for their efficiency in arsenic removal. However, most of these techniques are expensive, generates toxic sludge and requires skilled labor for operation (Sarkar and Paul, 2016).…”
Section: Introductionmentioning
confidence: 99%